2015
DOI: 10.1007/s00066-015-0817-3
|View full text |Cite
|
Sign up to set email alerts
|

DEGRO/DGK guideline for radiotherapy in patients with cardiac implantable electronic devices

Abstract: An increasing number of patients undergoing radiotherapy (RT) have cardiac implantable electronic devices [CIEDs, cardiac pacemakers (PMs) and implanted cardioverters/defibrillators (ICDs)]. Ionizing radiation can cause latent and permanent damage to CIEDs, which may result in loss of function in patients with asystole or ventricular fibrillation. Reviewing the current literature, the interdisciplinary German guideline (DEGRO/DGK) was developed reflecting patient risk according to type of CIED, cardiac conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 59 publications
0
72
0
4
Order By: Relevance
“…Recognizing the increasing number of pacemakerdependent patients diagnosed with cancer, several professional organizations and hospitals have recently published guidelines for radiotherapy in patients with ICDs, making recommendations for radiation dosage and appropriate follow-up. [12][13][14][15] Multiple retrospective case series have also considered the potential effect of radiation on ICDs with reported rates of inappropriate device function ranging between 1.5% and 29%. [14][15][16][17] In particular, it has been shown that neutronproducing radiotherapy, especially >10 MV, is associated with malfunction of contemporary implantable cardiac devices (ICDs and pacemakers).…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the increasing number of pacemakerdependent patients diagnosed with cancer, several professional organizations and hospitals have recently published guidelines for radiotherapy in patients with ICDs, making recommendations for radiation dosage and appropriate follow-up. [12][13][14][15] Multiple retrospective case series have also considered the potential effect of radiation on ICDs with reported rates of inappropriate device function ranging between 1.5% and 29%. [14][15][16][17] In particular, it has been shown that neutronproducing radiotherapy, especially >10 MV, is associated with malfunction of contemporary implantable cardiac devices (ICDs and pacemakers).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, new CIED models are constantly being introduced, with accumulated data on radiation resistance of existing CIEDs becoming outdated, especially in the context of modern irradiation techniques like tomotherapy, respiratory‐gated irradiation, or robotic radiosurgery . Useful guidelines and tips have been recently published by the German Society of Cardiology; however, these guidelines have not been proved in practice or by randomized trials but instead are based on the structure and function of the German health care system and expert consensus. According to those position papers, it is indicated to prepare patients to radiotherapy procedures in 3 steps which are summarized in Table .…”
Section: Practical Tips For the Time Of Radiationmentioning
confidence: 99%
“…Due to this fact, many studies have focused on the effect of radiotherapy on patients with CIEDs, and many aspects of this field have been investigated in the literature. [8][9][10] However, guidelines 11,12 and reviews 9,13 mainly address the management of patients with CIEDs undergoing conventional radiotherapy. 14,15 The first recommendation from the AAPM on the management of radiotherapy patients with CIEDs dates back to 1994 (TG-34).…”
Section: Introductionmentioning
confidence: 99%